Spectrum Analysis of Sound Wave Recordings with Dolphinear type DE200 Based on Distance and Frequency Variations in Mahakam River Using Audacity Software - Nurhanafi, Kholis; Mislan, Mislan; Zarkasi, Ahmad; Ariyanthi, Gita Putri; Purnama, Aditya Yoga; Saputra, Kormil (JPSE (Journal of Physical Science and Engineering), 2023)
Dolphinear is an instrument for monitoring sound wave signals underwater. This study aims to see how the results of sound recording by Dolphinear type DE200 based on variations in distance and frequency of the sound source using the Audacity Software. In this study, the sound source will be generated through a waterproof speaker with a frequency variation of 100 Hz to 20 kHz. The distance between the sound source and the dolphinear is also varied from 1 to 5 meters. Audacity software is used to generate, record, and obtain the spectrum of the recorded audio sound signal. Based on the spectrum of the sound recorded by the DE200 dolphinear, frequency peaks close to the source frequency can be detected in recording using a 500 Hz sound source, but the main frequency peaks in the spectrum are difficult to detect in recording using sound sources above 500 Hz. In this study, it was also found that there is a limit to the recording ability of the dolphinear DE200 for frequencies above 18 kHz which is indicated by a decrease in intensity at that frequency.